Risk factors for clinical failure of peroral endoscopic myotomy in achalasia - Quénéhervé, Lucille; Vauquelin, Blandine; Berger, Arthur; Coron, Emmanuel; Olivier, Raphael (Frontiers in Medicine, 2022)
The recent development of per oral endoscopic myotomy (POEM) has been a game changer in the management of patients with achalasia. However, approximately 1 in 10 patients will not experience clinical success. The aim of this mini-review is to describe the current state of knowledge about the risk factors associated with POEM failure for the treatment of achalasia. Suspected risk factors are detailed into pre-, intra-, and post-procedural factors and put into perspective. Pre-procedural factors have been described, such as pre-treatment Eckardt score, previous treatments for achalasia, sigmoid type esophagus, significant esophageal dilatation, non-type II achalasia, young age and long duration of symptoms. An intra-procedural factor, mucosal injury during POEM, has also been associated with POEM failure. The occurrence of post-POEM GERD was identified as a controversial post-procedural factor associated with failure. The presumed mechanisms of POEM failure are incomplete myotomy or ineffective LES disruption, as confirmed by high-resolution manometry. However, when manometry confirms a significant decrease in LES pressure, it is likely that either impaired peristalsis or a morphologic abnormality such as extreme esophageal dilatation or severe tortuosity, which are not treated by POEM, should be suspected. Notably, a recently described adverse effect of POEM is the formation of a pseudo-diverticulum at the site of the myotomy (blown out myotomy). We finally stress the importance of performing a complete workup in case of POEM failure as different mechanisms of POEM failure should lead to different management.